Utility of Stathmin-1 as a Novel Marker in Evaluating Anal Intraepithelial Neoplasia (AIN). Issue 2 (February 2019) - Hissong, Erika; Cimic, Adela; Leeman, Annemiek; Pirog, Edyta C.
Abstract : The aim of this study is to determine whether immunohistochemistry for Stathmin-1 enhances diagnostic accuracy of anal dysplasia. The study included 40 biopsies with diagnosis of benign anal transitional zone (n=10), low-grade anal intraepithelial neoplasia (AIN) (AIN1, n=10), and high-grade AIN (AIN2, n=10, AIN3, n=10). The cases were selected to represent classic features. Immunohistochemistry for Stathmin-1, p16, and Ki-67 was performed and assessed for distribution within epithelial thickness. Stathmin-1 was expressed only in the basal layer of benign anal epithelium. Similar pattern of distribution was seen in all low-grade AIN cases (100%). In total, 40% of AIN2 showed Stathmin-1 staining pattern similar to AIN1. The other 60% of cases showed staining extending into the middle third of the epithelial thickness. Of AIN3 cases, 20% showed staining confined to the lower third epithelium, 20% showed staining extending to the middle third, and 60% showed staining extending into the upper third epithelium. The pattern of stain distribution suggested that staining extending above the lower one-third of the epithelial thickness discriminates between low-grade and high-grade AIN. With this cutoff, the sensitivity for the diagnosis of high-grade AIN was 70%, specificity was 100%, positive predictive value equaled 100%, and negative predictive value equaled 77%. P16INK4a showed 100% sensitivity for AIN2 and AIN3, whereas Ki-67 had 100% sensitivity for any AIN grade. In conclusion, Stathmin-1 has excellent specificity for the diagnosis of high-grade AIN; however, Stathmin-1 alone may not be sufficiently sensitive. Use in conjunction with other sensitive markers, such as p16 or Ki-67 may be considered.